Functionally graded structures realized based on Fe–Mn–Al–Ni shape memory alloys. (15th March 2021) - Vollmer, M.; Bauer, A.; Kriegel, M.J.; Motylenko, M.; Niendorf, T.
Abstract: In the present study a novel approach to obtain functionally graded properties in an Fe–Mn–Al–Ni shape memory alloy is introduced. A single crystalline sample showing superelastic properties was aged in a partially martensitic state. As a result, the area aged in austenite is characterized by a changed superelastic hysteresis with different critical stresses for forward and backward transformation, whereas the properties in the area aged in martensite remained almost unchanged. Transmission electron microscopy studies revealed that the mean average size of nanometric β precipitates, which strongly influence the transformation temperatures and eventually the transformation stresses, is about 9 nm in the area aged in martensite and about 12 nm in the area aged in austenite. Based on these results it seems to be feasible to tailor Fe–Mn–Al–Ni components in a way allowing them to show locally different functional properties. Graphical abstract: Image, graphical abstract